ANALISIS KEMAMPUAN LITERASI TEKNOLOGI INFORMASI DAN KOMUNIKASI GURU FISIKA PADA SMA SE-KOTA MERAUKE - Syamsul Bahri; Mitra Rahayu; Desy Kumala Sari; Merta Simbolon (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2020)
A physics teacher needs information and Communication Technology (ICT) literacy skills in teaching and learning in the classroom. This study aims to analyze the ICT literacy skills of high school physics teachers in Merauke city. This type of research is descriptive quantitative research. Respondents involved in this study were 19 high school physics teachers in Merauke City (Merauke District). The instrument used to collect data was an ICT literacy ability questionnaire developed by researchers totaling 40 statements. The research data were processed using descriptive statistical analysis techniques by determining the percentage of respondents' responses. The analysis showed that the average rate of ICT literacy skills in high school physics teachers was 87%. This means that in general, the ICT literacy skills of high school physics teachers in Merauke City are in the "excellent" category.